CAREER MATURITY AMONG ADOLESCENTS IN RELATION TO THEIR SCHOOL CLIMATE (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
The present study was undertaken with the purpose of studying career maturity of adolescents in relation to their school climate. This study was conducted on a sample of 800 adolescents studying in secondary schools of Amritsar District. The results indicates that out of six dimensions of career maturity, only three dimensions namely self appraisal, occupational information and problem solving show significant difference with high, average and low levels of school climate.